2023
DOI: 10.3389/fcell.2023.1052942
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA and its role in gastric cancer immunotherapy

Abstract: Gastric cancer (GC) is a potential dominant disease in tumor immunotherapy checkpoint inhibitors, and adoptive cell therapy have brought great hope to GC patients. However, only some patients with GC can benefit from immunotherapy, and some patients develop drug resistance. More and more studies have shown that long non-coding RNAs (lncRNAs) may be important in GC immunotherapy’s prognosis and drug resistance. Here, we summarize the differential expression of lncRNAs in GC and their impact on the curative effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Although the function of lncRNA THUMPD3-AS1 in tumors is unknown, 30 , 31 it has been reported to be significantly elevated in a variety of cancer tissues, and studies have shown that THUMPD3-AS1 enhances the proliferation and invasiveness of colorectal, non-small-cell lung, and hepatocellular carcinoma cells. 32 , 33 These results suggest that THUMPD3-AS1 is commonly highly expressed in tumors with proto-oncogene characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Although the function of lncRNA THUMPD3-AS1 in tumors is unknown, 30 , 31 it has been reported to be significantly elevated in a variety of cancer tissues, and studies have shown that THUMPD3-AS1 enhances the proliferation and invasiveness of colorectal, non-small-cell lung, and hepatocellular carcinoma cells. 32 , 33 These results suggest that THUMPD3-AS1 is commonly highly expressed in tumors with proto-oncogene characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…They exhibit highly specific lineage, spatiotemporal, and tissue/cell-dependent patterns, but their abundance, stability, and conservation are less than mRNA (50, 51). LncRNAs are essential modulators that participate in almost every step of gene expression (52,53). Their canonical mechanism of action is to inhibit target gene expression by binding to miRNA and imposing an additional post-transcriptional regulation level.…”
Section: Lncrnamentioning
confidence: 99%
“…The intricate interplay between GC and lncRNAs pivots around the complex regulation of gene expression and diverse cellular processes [ 19 ]. Emerging evidence has implicated dysregulation of certain lncRNAs in the pathogenesis and progression of GC [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%